PERAN UPT P2TK PROVINSI JAWA TIMUR DALAM IMPLEMENTASI PELINDUNGAN DAN PELAYANAN PADA PEKERJA MIGRAN INDONESIA DI LUAR NEGERI SESUAI AMANAT UU NO. 18 TAHUN 2017: THE ROLE OF UPT P2TK OF EAST JAVA PROVINCE IN IMPLEMENTING PROTECTION AND SERVICES FOR INDONESIAN MIGRANT WORKERS ABROAD IN ACCORDANCE WITH THE MANDATE OF LAW NO. 18 OF 2017 - poltekim, Gerald Dimas Siswanto; Anggita Pramesti; Rafil Ibnu Sabil; Muhammad Charis Shofil (Journal of Administration and International Development, 2025)
Abstract This study analyzes the role of the Technical Implementation Unit for Worker Services and Protection (UPT P2TK) in implementing protection and services for Indonesian Migrant Workers (PMI) in accordance with the mandate of Law Number 18 of 2017. The main focus of this study is the legal and administrative protection efforts for PMI carried out during the pre-placement, placement, and post-placement periods. The results of the study indicate that UPT P2TK has a very strategic role in providing legal counseling, pre-departure briefing, document verification, pre-departure briefing, and coordination with the Indonesian Embassy (KBRI) in handling problematic PMI cases. However, in its implementation, it still faces structural challenges, limited human resources, and limited policy synchronization between central and regional institutions. These results are expected to be a reference in improving a comprehensive and sustainable PMI protection system..